PERJUMPAAN KEILMUAN ISLAM DENGAN ILMU PENGETAHUAN BARAT - Hardika Saputra (Insititut Agama Islam Agus Salim Metro Lampung, 2021)
The most rapid development of science in Islam occurs when the Muslims met with the culture and civilization has advanced from the nations they conquered. The development is increasingly clear since the beginning of the reign of Bani Abbas in the mid 8th century. The transfer of the capital Damascus (Damascus) located in the Arab neighborhood of Baghdad that was in the Persian neighborhood who already have a high scientific culture and are familiar with Greek science and philosophy, became the tool trigger splendor scientific spirit that has been owned by the Muslims. There is a phenomenon that appears in society, Islamic education is a utopian concept that cannot be realized, really this is a wrong view of understanding in understanding Islamic education. Because Islamic education runs within a clear and realistic frame of reality in society. However, Islamic education is based on Islamic ideals which are sometimes misunderstood by the implementers of Islamic education. As a result, the idealism of Islamic education is seen as an institution that prioritizes the values of hereafter and does not care about the existing reality. Strictly speaking, Islamic education is education that goes hand in hand with developments in society and still maintains Islamic values as its foundation.